Testing Predicitive Ability of Business Cycle Indicators for the Euro Area - Christina Ziegler (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2009)
We analyze the predictive power of seven leading indicators for economic activity inthe Euro Area developed by different banks, institutions and research centers. Ourcomparison is conducted in a bivariate vector autoregressive framework. Indicators arecompared by means of an in-sample and an out-of-sample forecasting experiment.Predictive accuracy is compared by recently proposed tests for superior predictive ability.Our results suggest that nearly all indicators have good in-sample properties and that amajority of them is able to outperform a naive univariate autoregressive model out-of-sample.Additionally, we find that indicators perform better in boom periods than inrecessions. The OECD and FAZ indicators are both composite indicators and deliver themost accurate forecasts.
Keywords: C32; C53; E32; 330; Leading indicators; Euro area; forecasting; Konjunkturindikator; Konjunkturprognose; Prognoseverfahren; VAR-Modell; Statistischer Test; Europäische Wirtschafts- und Währungsunion